2019
DOI: 10.1186/s42480-019-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy and CO2 management for chemical and related industries: issues, opportunities and challenges

Abstract: This paper gives a brief review of energy and CO 2 emissions related topics resulting from the chemical and related industries. The main issues, challenges and opportunities are highlighted together with perspectives of process alternatives for more efficient energy consumption and CO 2 emission management. Analysis of the data indicate that not all available energy resources are being utilized efficiently, while the energy resources causing the largest emissions of CO 2 are being used in the largest amounts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…However, there is a clear lack of research in industrial symbiosis networks that integrate renewable energy, which was observed by Butturi et al (2019). In addition, there is a need to combine emission reduction technologies with improving energy and resource use efficiency in chemical industries (Vooradi et al, 2019). Therefore, this work aims to address these gaps, utilizing the model developed by Ahmed et al (2020) with the goal of designing a carbon neutral industrial park to produce value-added products from free or waste resources (seawater, air, sunlight, and carbon dioxide).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a clear lack of research in industrial symbiosis networks that integrate renewable energy, which was observed by Butturi et al (2019). In addition, there is a need to combine emission reduction technologies with improving energy and resource use efficiency in chemical industries (Vooradi et al, 2019). Therefore, this work aims to address these gaps, utilizing the model developed by Ahmed et al (2020) with the goal of designing a carbon neutral industrial park to produce value-added products from free or waste resources (seawater, air, sunlight, and carbon dioxide).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical processing industry manufacturing products by mixing, separating, forming, and chemical reactions, is being promoted for its greatly important contribution to economic development, providing high quality products to many sectors, such as building, transportation, construction and health [1]. It is also the largest energy consumer among industrial sectors with 1078 million tons of oil equivalent of energy consumption in the year 2016 [2]. Unlike general artificial intelligence which builds computerized systems possessing intelligence like humans, industrial intelligence is more concerned with the application of technologies to build a smart system that can adapt to the changes in industrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important goals of today's society is the transition from a fossil fuelbased economy to a sustainable bioeconomy with the aim of mitigating global greenhouse gas (GHG) emissions, the alarming increase in global energy demand, and the exhaustion of fossil fuel reserves [1]. In this context, biomass is a renewable source with constant global availability that can be used for the manufacture of a wide variety of bio-products, including chemicals, materials, food, and feed [2].…”
Section: Introductionmentioning
confidence: 99%